Magnetically-actuated micromechanical nickel patches for a monolithically integrated reconfigurable antenna on printed circuit board. (3rd October 2019) - Pal, Jitendra; Donzelli, Francesco; Santhanam, Suresh; Deshpande, Kaustubh; Chomas, Lou; Piazza, Daniele; Bain, James A; Piazza, Gianluca
Abstract: In this paper, we present magnetically-actuated micromechanical Ni patches that have been monolithically integrated on a printed circuit board to demonstrate a reconfigurable pixelated antenna operating within the 5–8 GHz frequency bands. The proposed antenna is based on a monolithically integrated grid structure of movable nickel (Ni) and fixed copper (Cu) patches. The Ni patches are magnetically actuated by means of an array of switchable magnets (SMs) placed behind the ground plane of the antenna. This approach eliminates the need for bias lines, which are generally used in reconfigurable antennas and induce losses. Most importantly, the very low mechanical contact resistance (as low as 200 mΩ) between the Ni and Cu patch ensures the insertion of these devices on the antenna plane without introducing significant losses. The use of a SM for the actuation of the patch makes it such that the antenna can hold the desired configurations without consuming active power. Power is consumed only during the switching operation. To demonstrate the feasibility of the proposed idea, the four most relevant operating modes of this small antenna prototype, centered around 5.55 GHz, 6.44 GHz, and 7.89 GHz, are presented.